Peran POSYANDU Jiwa dalam Penguatan Nilai Kemanusiaan di Desa Pertapan Maduretno, Sidoarjo - Wulandari Ratnasati; Raden Roro Nanik Setyowati (Kajian Moral dan Kewarganegaraan, 2023)
The purpose of this study was to analyze in depth the role of the mental health post in improving the quality of life of people with mental disorders in order to achieve human values ​​in the village of Pertapan Maduretno and the obstacles that occur. In this study, Biddle and Thomas' role theory was used. This type of research is qualitative research with a qualitative descriptive research design. Data collection techniques in this study used in-depth interviews, observation, and documentation, as well as research informants selected by purposive sampling method were mental health midwives and mental health cadres. The focus of this research is to analyze the role and inhibiting factors of the mental health post in carrying out its role. The results of this study explain that the role of mental health services in increasing human values ​​can be seen in socialization and public education regarding people with mental disorders, the implementation of treatment for patients with direct methods, home visit treatment services, and the provision of creativity services as a therapeutic medium to patients. The inhibiting factors for the role of the mental health post in increasing human values ​​come from the family's mindset in refusing, the anxiety of the patient, and the termination of activities due to the Covid-19 pandemic. Keywords: Role, Humanity, Human Rights